Characteristic morphology and genetic variability of Benggala grass (Panicum maximum cv Purple guinea) through gamma ray irradiated on acid land - Achmad Fanindi; S. H. Sutjahjo; S. I. Aisyah; N. D. Purwantari (Indonesian Center for Animal Research and Development (ICARD), 2016)
The induction mutation using gamma rays is one way to increase the diversity of Bengggala grass (Panicum maximum). Diversity is the main base in selecting to produce varieties of Benggala grass on acid land. The aim of this study is to know the morphological character and genetic diversity of grass that received gamma rays. The research was conducted in the Tenjo district, Bogor which has pH 4.9-5.5 and the content of Al-dd 2.26 c mol/kg with Al saturation of 10.68%. The study started by looking for Benggala grass radio sensitivity, then from radio sensitivity determined radiation treatment dose of 200 Gy, 250 Gy, 300 Gy and 350 Gy. Treatment of radiation dose is acute and fractionated, so there are 8 treatment doses plus control (plants without radiation). The variables measured were plant height, stem height, stem diameter, length of segment, leaf length, leaf width, fresh weight, dry weight, and number of tillers. The results showed that the radio sensitivity of Benggala grass produced in the form of lethal doses (LD) LD 20 and LD50 is 176.83 Gy and 358.23 Gy. By the mathematical equation: Y = 44.22 + 45.91 X Cos (0.0042x -0.07). The morphological character of M1 shows that the radiation dose affects the measured variable. 300 Gy fractionated radiation dose (150 Gy x 2) results in higher fresh weight of the plant. While in the generation of M1V1 radiation dose of 250 Gy produces high fresh forage weight. Medium to high heritability with GVC value (criteria of coefficient of genetic variability) is high enough until high is obtained on the character of the number of tillers, fresh weight and dry weight. So it is possible to do next selection on these three characters.